Indacenodithiophene–benzothiadiazole organic field-effect transistorswith gravure-printed semiconductor and dielectric on plastic - Campbell,AJ; Higgins,SG; Muir,BVO; Heeney,M (MRS Communications, 2015)
We demonstrate the gravure printing of a high-performance indacenodithiophene (IDT) copolymer, indacenodithiophene–benzothiadiazole (C16IDT–BT), onto self-aligned organic field-effect transistor architectures on flexible plastic substrates. We observed that the combination of a gravure-printed dielectric with gravure-printed semiconductor yielded devices with higher mean-effective mobility than devices manufactured using photolithographically patterned dielectric. Peak mobilities of μ = 0.1 cm2 V−1 s−1 were measured, and exceed previous reports for non-printed C16IDT-BT on non-flexible silicon substrates.